Effect of Layer Thickness on the Physical and Mechanical Properties of Sand Powder 3D Printing Specimens - Xu, Qing; Jiang, Lishuai; Ma, Changqing; Niu, Qingjia; Wang, Xinzhe (Frontiers in Earth Science, 2021)
The application of sand-powder 3D printing technology in the field of rock mechanics and mining engineering has tremendous potential, but it is still in the preliminary exploration stage. This study investigated the effect of printing layer thickness on the physical and mechanical properties of rock-like specimens with sand-powder 3D printing. Quartz sand powder was used as the printing materials, and the specimens were prepared with three different layer thickness of 0.2 mm, 0.3 mm, 0.4 mm. Uniaxial compression test with a combination of digital image correlation (DIC), acoustic emission (AE) and three-dimension microscope observations were performed to analyze mechanical properties and failure patterns of specimens during the loading. Experimental findings showed that increment of layer thickness from 0.2 mm to 0.4 mm would result in a decrease of the weight, density, uniaxial compression strength (UCS), and elastic modulus of specimens. The stress-strain curve, deformation and failure patterns, crack growth process and AE characteristics of the specimens with a layer thickness of 0.2 mm are similar to those of rock-like material, whereas the specimens with layer thickness of 0.3 mm and 0.4 mm deform like a ductile material, which is not appropriate for simulation of coal or rock mass. In the future study, rock-like specimens should be prepared with small layer thickness.